Performance of Three Isolates of Metarhizium anisopliae and Their Virulence against Zeugodacus cucurbitae under Different Temperature Regimes, with Global Extrapolation of Their Efficiency - Onsongo, Susan K.; Gichimu, Bernard M.; Akutse, Komivi S.; Dubois, Thomas; Mohamed, Samira A. (MDPI, 2019)
The performance of entomopathogenic fungi in pest control is usually a ected by both biotic and abiotic factors. This study aimed to determine the e ects of various temperatures (15, 20, 25 and 30 C) on conidial germination, mycelial growth and conidial density and virulence to the melon ﬂy Zeugodacus cucurbitae of three selected isolates of Metarhizium anisopliae. The three isolates, ICIPE 18, ICIPE 30 and ICIPE 69, had previously been selected in laboratory bioassays. Percentage mortality by the three isolates ranged between 16.25% and 100.0% across the di erent temperatures. The isolates ICIPE 69 and ICIPE 18 recorded the highest percentage mortality of 96.25% and 100% and the shortest LT50 values of 2.61 and 2.63 days, respectively, at 30 C, ICIPE 69 produced the highest number of conidia of 90.5 10 C. However, at 30 /mL and was therefore selected for global mapping to predict its e cacy against Z. cucurbitae using the geospatial temperature data layer and the best ﬁtted quadratic model. The map showed that the isolate would be more e ective in the tropics than in temperate climates.
Keywords: entomopathogenic fungus; germination; melon ﬂy; percentage mortality; radial growth; sporulation